2012
DOI: 10.1002/alr.21028
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of intravenous ketorolac in patients undergoing primary endoscopic sinus surgery: a randomized, double‐blinded clinical trial

Abstract: In this study, IVKT was a safe analgesic in the setting of primary ESS. There was no increased risk of hemorrhage or acute blood-loss anemia. IVKT did not appear to offer statistically significant pain control over IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Church et al randomized 28 FESS patients and gave either rofecoxib or hydrocodone/acetominophen after surgery and found equivalent postoperative pain control in the 2 groups . In another randomized, controlled trial, Moeller et al compared intraoperative intravenous ketorolac with fentanyl and found them to be equivalent for pain control perioperatively, with no significant change in bleeding or complications . Our study included 101 patients who were recommended ibuprofen, and there were no bleeding complications, further supporting the evidence of a lack of increased bleeding with NSAID use postoperatively.…”
Section: Discussionsupporting
confidence: 67%
“…Church et al randomized 28 FESS patients and gave either rofecoxib or hydrocodone/acetominophen after surgery and found equivalent postoperative pain control in the 2 groups . In another randomized, controlled trial, Moeller et al compared intraoperative intravenous ketorolac with fentanyl and found them to be equivalent for pain control perioperatively, with no significant change in bleeding or complications . Our study included 101 patients who were recommended ibuprofen, and there were no bleeding complications, further supporting the evidence of a lack of increased bleeding with NSAID use postoperatively.…”
Section: Discussionsupporting
confidence: 67%
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Other alternatives for pain control have been proposed as well. In a randomized clinical trial by Moeller et al, no differences in postoperative epistaxis rates were found in patients who received intravenous ketorolac compared to intravenous fentanyl during FESS procedures . Kim et al proposed an alternative technique utilizing topical anesthesia; this study demonstrated significantly lower reported pain and increased patient satisfaction following FESS and septoplasty procedures when patients were given topical fentanyl‐soaked nasal packing compared to saline soaked packing …”
Section: Discussionmentioning
confidence: 99%